The effect of the physical activity on polymorphic premature ventricular complexes in chronic kidney disease - Márcio G. Kiuchi; Shaojie Chen (The Korean Society of Nephrology, 2017)
Background: Polymorphic premature ventricular complexes (PVCs) are very common, appearing most frequently in patients with hypertension, obesity, sleep apnea, and structural heart disease. Sympathetic hyperactivity plays a critical role in the development, maintenance, and aggravation of ventricular arrhythmias. Endurance exercise training clearly lowers sympathetic activity in sympatho-excitatory disease states and may be tolerated by patients with chronic kidney disease (CKD). Methods: We assessed 40 CKD patients with hypertension with polymorphic PVCs. Patients underwent a complete medical history and physical examination. We evaluated the effectiveness of β blocker only or β blocker + exercise during 12 months of follow-up regarding the changes of the numbers of PVCs and mean heart rate (HR) by 24-hour-Holter. Results: We observed in the β blocker group a significant decrease in the number of polymorphic PVCs from baseline 36,515 ± 3,518 to 3, 6, 9 and 12 months of follow-up, 28,314 ± 2,938, 23,709 ± 1,846, 22,564 ± 1,673, and 22,725 ± 1,415, respectively (P < 0.001). In the β blocker + exercise group a significant decrease in the number of polymorphic PVCs also occurred from baseline 36,091 ± 3,327 to 3, 6, 9 and 12 months of follow-up, 29,252 ± 3,211, 20,948 ± 2,386, 14,238 ± 3,338, and 6,225 ± 2,319, respectively (P < 0.001). Comparisons between the two groups at the same time point showed differences from the sixth month onwards: the 6th (Δ = −2,761, P = 0.045), 9th (Δ = −8,325, P < 0.001) and 12th (Δ = −16,500, P < 0.001) months. There was an improvement during the 12 months of follow-up vs. baseline, after the β blocker or β blocker + exercise in mean 24-hour HR Holter monitoring, creatinine values, eGFR, and ACR. Conclusion: Polymorphic PVCs may be modifiable by physical activity in CKD patients with hypertension without structural heart disease.